JDICOM java-implemented digital imaging and communications in medicine - Arboleda, Eugene Jose L.; Chan, Allen R.; Correos, Mark Lawrence A.; Estrella, Patrick Brian T.; Garcia, Nelson R. (2001)
The world today lives in a different mode of communication. We no longer use messengers that travel across lands for days, weeks or months. We use modes of communication that shorten the waiting time. Today, people exchange ideas and information through the Internet in a matter of minutes or even seconds. The field of medicine deals with the lives of people. It is just right for its disciplines to use every possible way to help their patients in need. If they need to ask for the advice and help of their fellow disciples then they should do it by all means. This project helps to realize this aspect. That every medical person should be able to communicate with their fellow medical practioners, wherever and whenever he wants to, with the help of today's most powerful means of communications - the Internet. Our study is an implementation of the medical industry's standard of communications - the Digital Imaging and Communications in Medicine, using Java, a platform-independent language that will help hospitals use the standard in any platform or operating system that they want to use. The implementation includes database management for all users, a chat room where users can discuss medical images, a file transfer feature and most importantly a DICOM image viewer that will allow users to manipulate the images.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Internet in medicine; Medicine -- Communication systems; Digital imaging and communications in medicine (DICOM).; JDICOM (Computer program).